MANAJEMEN PEMBIAYAAN BANTUAN OPERASIONAL SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN PONDOK PESANTREN - Mazidah, Siti (J-MPI (Jurnal Manajemen Pendidikan Islam), 2018)
. Financing is one of the keys to implementing an education. One source of funding sourced from the government is the School Operational Assistance (BOS) program. The purpose of this study was to: (1) describe the distribution of BOS funds in the education of Islamic boarding schools in the Ministry of Religion Office in Malang Regency, (2) explain the supervision of BOS funding in Islamic boarding school education, (3) describe the implications of BOS funding in improving quality Islamic boarding school education. This study uses a qualitative approach with a type of case study research. Data collection techniques used were observation, interviews, and documentation. Data is analyzed by reducing relevant data, describing and drawing conclusions. The results showed that, (1) the distribution of funding for BOS funds in the education of Islamic boarding schools in the Malang Ministry of Religion Office was carried out in accordance with the flow, (2) supervision of BOS funding in improving the quality of Islamic boarding school education was carried out according to the time of disbursement at the time of reporting of BOS funds, namely by direct and indirect supervision, (3) Implications of BOS funds in improving the education quality of Islamic boarding schools, namely: improving student achievement and learning outcomes and increasing teacher welfare.